1980
DOI: 10.1083/jcb.84.3.753
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Schwann cell proliferation. II. Characterization of the stimulation and specificity of the response to a neurite membrane fraction.

Abstract: When prepared by methods utilized in our laboratory, pure populations of Schwann cells in culture do not divide, but, after recombination with peripheral sensory neurons or their processes, proliferate rapidly (Wood and Bunge, 1975, Nature (Lond) 256:661-664). In this paper, we demonstrate that a membrane fraction prepared from sensory ganglion neurites is also mitogenic for Schwann KEY WORDS Schwann cell proliferation mitogenic signal . nerve tissue culture membranes " autoradiography In the first paper of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
2
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(121 citation statements)
references
References 22 publications
3
115
2
1
Order By: Relevance
“…The mitogenic effect resulting from synergy between PITF, CT and FCS [5] is three times higher than that observed with neurite membrane fraction from sensory neurons [33,34]. The combined use of PITF and CT, has resulted in the accumulation of millions of cells with CT phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitogenic effect resulting from synergy between PITF, CT and FCS [5] is three times higher than that observed with neurite membrane fraction from sensory neurons [33,34]. The combined use of PITF and CT, has resulted in the accumulation of millions of cells with CT phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that SC indefinitely preserve their potential of migration even when they are fixed in the adult nerve. Migration resumes if nerve degeneration occurs [32].The mitogenic effect resulting from synergy between PITF, CT and FCS [5] is three times higher than that observed with neurite membrane fraction from sensory neurons [33,34]. The combined use of PITF and CT, has resulted in the accumulation of millions of cells with CT phenotype.…”
mentioning
confidence: 99%
“…Neuregulins are produced by neurons (Marchionni et al, 1993;Dong et al, 1995) in a variety of splice variant transcripts, some of which encode a membrane-bound ligand (Marchionni et al, 1993). Immunohistochemical studies demonstrate neuregulins within axons , and neuronal membrane preparations stimulate the growth of cultured Schwann cells (Salzer et al, 1980) through the activation of p185 erbB2 (Morrissey et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Membrane Purification-Sensory neuron membranes were isolated from DRG neurons, initially plated as explants but treated with cytosine arabinoside to remove all non-neuronal cells as described before (13,18) with modifications. The neurons were rinsed in PBS, and cell bodies were excised using a scalpel under a dissecting microscope.…”
Section: Methodsmentioning
confidence: 99%